1998
DOI: 10.1007/s004410051145
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of kynurenine and tryptophan treatment on quinolinate immunoreactivity in rat lymphoid and non-lymphoid organs

Abstract: Quinolinate is a tryptophan metabolite and an intermediary in nicotinamide adenine dinucleotide (NAD+) synthesis in hepatocytes. Kynurenine is an upstream metabolite in the same biochemical pathway. Under normal physiological conditions, kynurenine is thought to be produced primarily in the liver as an NAD+ precursor. However, during immune stimulation or inflammation, numerous extrahepatic tissues convert systemic tryptophan to kynurenine, and its concentration subsequently rises dramatically in blood. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…While it is likely that Quin-IR cells express active kynurenine pathway enzymes from IDO to QPRT, it is possible that not all cells require IDO expression. Our experiments involving tryptophan and kynurenine loading in rats indicate that many cells of the immune system avidly take up kynurenine and convert it to Quin in <3 h (29). This suggests that cells such as fibroblasts that release kynurenine (45) may feed Quin synthesis and NAD + production in other cell types.…”
Section: Quin-ir In Rat Brainmentioning
confidence: 86%
See 1 more Smart Citation
“…While it is likely that Quin-IR cells express active kynurenine pathway enzymes from IDO to QPRT, it is possible that not all cells require IDO expression. Our experiments involving tryptophan and kynurenine loading in rats indicate that many cells of the immune system avidly take up kynurenine and convert it to Quin in <3 h (29). This suggests that cells such as fibroblasts that release kynurenine (45) may feed Quin synthesis and NAD + production in other cell types.…”
Section: Quin-ir In Rat Brainmentioning
confidence: 86%
“…The digital images presented here were generated from archival slides prepared previously and include material from both published (25)(26)(27)(28)(29) and unpublished studies. The methods used for the production, purification, and characterization of the polyclonal Quin antibodies have been described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Moffett et al have shown that intraperitoneal injections of Kyn did not result in any significant increase in hepatocyte immunoreactivity with quinolinate-specific antibody, but rather led to dramatic increase in immunoreactivity in tissue macrophages, splenic white pulp, and thymic medulla [43,44]. Quinolinic acid formation was also induced most strongly in spleen by systemic immune stimulation with pokeweed mitogen [45].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, kynurenine and 3‐hydroxykynurenine and xanthurenic acid, which is a product of a PLP‐dependent reaction, contribute to development of immunotolerence in airway inflammation in allergic asthma . Additional evidence for involvement of PLP‐dependent reactions of the kynurenine pathway in immune response comes from the accumulation of quinolate (Figure ) at micromolar concentrations or greater in lymphoid tissues and macrophages during immune response . Thus, it appears that tryptophan degradation via PLP‐dependent reactions is involved in developing immune tolerance, suppression of inflammation, and reducing tissue damage due to immune response.…”
Section: Proposed Role Of Plp In Inflammationmentioning
confidence: 99%